Cover Picture: Electron Spin-Dependent Electrocatalysis for the Oxygen Reduction Reaction in a Chiro-Self-Assembled Iron Phthalocyanine Device (Angew. Chem. Int. Ed. 4/2024) - Zagal-Moya, J; Zagal-Moya, J; Aspee-Lamas, A; Ponce-Hormazabal, I; Barrías-González, P; Mura-Mardones, F; Scarpetta-Pizo, L; Scarpetta-Pizo, L; Venegas-Toledo, R; Mendez-Torres, A; Mendez-Torres, A; Onate, R (WILEY-V C H VERLAG GMBH, 2024)
Sin Resumen Disponible